Attending to STEM education in servingness at Hispanic-serving institutions: a systematic review of more than a decade of scholarship - Hyun Kyoung Ro; Stephanie Aguilar-Smith; Shirley Yang Anderson; Tricia Rodriguez; Elizabeth J. Ramon; Damaris Javier (SpringerOpen, 2024)
Abstract Background, context, and purpose of the study Enrolling over 60% of all Latinx undergraduate students, Hispanic-serving institutions (HSIs) are poised to play a critical role in diversifying and strengthening Science, Technology, Engineering, and Mathematics (STEM) education and the STEM workforce. However, how HSIs serve STEM students is not well understood. Accordingly, guided by Garcia et al. (Review of Educational Research 89:5-745, 2019) multidimensional servingness framework, we conducted a systematic review of the research on STEM education within the HSI context. By attending to STEM education in conversations around how HSIs may serve Latinx students and their campus communities, our ultimate aim is to improve STEM education particularly at HSIs and advance STEM servingness more broadly. Results, main findings Through our systematic review of STEM education research at HSIs, we identified (under)studied components of servingness and gaps within this literature base. Specifically, among the 128 qualifying articles, nearly two-thirds focused on student outcomes but overlooked institutions' organizational context, raising questions about the effect(iveness) of the studied interventions. Additionally, we identified three thematic gaps in this literature: ghosting the HSI context (i.e., relying on HSIs as research sites without considering the unique HSI context); ghosting Latinx culture (i.e., decentering Latinx students and the Latinx community's sociocultural aspects and assets), and ghosting people and places (i.e., under-examining certain student populations like Latino men in STEM and places like Hispanic-serving community colleges). Ultimately, our study extends the field's understanding of servingness by attending to STEM education within the context of HSI institutions. Conclusions, brief summary, and potential implications By systematically reviewing studies on STEM education at HSIs, we identified (under)studied components of servingness and patterned gaps within this literature. In doing so, we highlight opportunities to advance STEM servingness at HSIs through future research, policy, and practice. Collectively, these avenues hold the promise of improving STEM education and diversifying the STEM workforce.